2021
DOI: 10.1111/jcal.12639
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐based self‐monitoring system for on‐task behavior of students with disabilities: A quantitative meta‐analysis of single‐subject research

Abstract: Background: There have been several studies that involved technology-based selfmonitoring procedures to increase on-task behavior. Although there are continued advancements in technology application such as functions that are embedded in the application (e.g., reinforcement, feedback), the appropriate use of technology is required to be accompanied by evidence-based guidance.Objectives: The purpose of this meta-analytic approach was to (a) examine the effectiveness of a technology-based self-monitoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Research has shown that self-monitoring is successful for students with LD, EBD, and ADHD (Bedesem, 2012; McDougall et al, 2017) and can be used effectively in specialized education settings (Ennis et al, 2018), as well as across behaviors (Bedesem, 2012). Systematic research reviews and meta-analyses indicate that although self-monitoring is used to increase academic performance and accuracy, it is most frequently used to address on- and off-task behaviors (Briesch et al, 2019; Bruhn, McDaniel, & Kreigh, 2015; Fishley & Bedesem, 2014; Mize et al, 2022). In addition to being versatile, self-monitoring is especially conducive to classroom settings because the strategy can be tailored for specific students according to the teacher’s design.…”
Section: Self-monitoringmentioning
confidence: 99%
“…Research has shown that self-monitoring is successful for students with LD, EBD, and ADHD (Bedesem, 2012; McDougall et al, 2017) and can be used effectively in specialized education settings (Ennis et al, 2018), as well as across behaviors (Bedesem, 2012). Systematic research reviews and meta-analyses indicate that although self-monitoring is used to increase academic performance and accuracy, it is most frequently used to address on- and off-task behaviors (Briesch et al, 2019; Bruhn, McDaniel, & Kreigh, 2015; Fishley & Bedesem, 2014; Mize et al, 2022). In addition to being versatile, self-monitoring is especially conducive to classroom settings because the strategy can be tailored for specific students according to the teacher’s design.…”
Section: Self-monitoringmentioning
confidence: 99%
“…Considering that students may find the frequent prompted monitoring during a task to be more intrusive and less motivating than monitoring after the task [ 31 ], it remains unclear whether frequent, prompted SM leads to sustainable changes in student behavior. Furthermore, Mize et al [ 32 ] recommended that future researchers investigate SM applications incorporating effective instructional components, such as reinforcement and error correction delivered by a teacher. Further research is necessary to evaluate whether SMP interventions that involve reinforcement without prompts and include teacher-delivered instructional components (i.e., reinforcement and error correction as needed) will yield similar behavioral improvements for students with disabilities, and whether these behavior changes will maintain over time.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, most SM procedures and recording devices were characterized by their simplicity and low-tech nature, relying on materials such as paper, pencil, timers, and buzzers to record student behavior [ 17 , 32 ]. However, utilizing such materials can produce social stigmatization, lead to embarrassment for students, and pose a greater investment of teacher time and materials to prepare [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations